Human behavior among motorcyclist: comparison between disc brake and drum brake of rear tire of motorcycle using hand brake type and leg brake type / Tengku Syazwan Tengku Bakry Shah - Tengku Bakry Shah, Tengku Syazwan (2010)
Human behavior falls within a range with some behavior being common, some c unusual, some acceptable and some outside acceptable limits. Human behavior is totally human action which is reaction of human mind to make decision. Understanding human behavior is one of important things which in learning experience of the past. Human behavior is related to safety issues when comes to riding motorcycle in phase of braking system. The purposes of this study are to identify and to analyze human behavior on braking system of rear tire between using hand brake type or leg brake type brake. However if the parameter is different which mean by using drum and disc brake is used for the rear tire will it effect on their behavior when braking. This type of study can be analyze through several methods which are by doing or distributing questionnaire, conduct an observation, taking pictures and video recording. Finally, carry out an interviewing session between motorcyclist and others that can be related to achieve and obtain the results needed. Motorcyclists are randomly selected from mechanical student which around 200 students for batch 2007. In addition, interview of motor trader sellers and workshop workers to have conducted in order to get more information of which type of motorcycles are most purchased. Throughout these methods, all the responses and findings can be evaluate in order to complete the objectives of my project.